Development and application of PyeongChang 2018 Winter Olympic and Paralympic Games Accessibility Manual. (19th May 2021) - Lee, Hye Lim; Kim, Ji Young; Kim, Jong Bae
Abstract: Introduction: In this study, the process of development, application, and evaluation of the PyeongChang Organising Committee for the 2018 Olympic and Paralympic Winter Games(POCOG) Accessibility Manual was introduced and the basic data for accessing venues and ways to improve accessible sporting event management were suggested. Methods: Analysing and comparing the IPC Guide and Korean accessibility laws with eight advisory meetings were held to develop "POCOG Accessibility Manual". To verify the Manual standards, accessibility assessment of the Paralympic Test-event, Olympic and Paralympic Games was conducted. Results: POCOG Accessibility Manual was developed based on the best practice of accessibility standards and feedback from various experts. Throughout the three-step verifications, many findings have resulted in the final recommendations for the improvements in the operation of the Olympic and Paralympic Games accessibility. Conclusions: The study provided fundamental data to develop an inclusive game operation manual for future international sports competitions, and it could ultimately serve as a cornerstone for integration and inclusion through sports. Implications for Rehabilitation: Ensuring accessibility can secure equal opportunities to participate and enjoy the events for everyone in mega-sporting events including persons with disabilities. However, the current Korean construction law does not adequately address the accessibility requirements for the Paralympic Games. Therefore, the study of the development of the 2018 Pyeongchang Accessibility Manual based on IPC guidelines was important. In this study, the 2018 Pyeongchang Accessibility Manual was applied and evaluated according to the planning stage of the 2017 Paralympic test-events, PyeongChang 2018 Winter Olympic and paralympic Games. The result derived from our study will provide a strategy to ensure the accessibility for persons with disabilities to countries hosting future sports events.